Rapid detection of the mecA gene in methicillin-resistant staphylococci by enzymatic detection of polymerase chain reaction products. - Ubukata, K (1992)
In order to identify methicillin-resistant staphylococci from clinical sources with ease and reliability, enzymatic detection of polymerase chain reaction (ED-PCR) was applied. ED-PCR is based on the capture of amplified products via biotin-streptavidin affinity and the detection of an incorporated hapten in amplified products with an enzyme-linked antibody. In order to identify methicillin-resistant staphylococci of all species, a 150-bp fragment of the mecA gene was targeted for ED-PCR. After PCR was performed with a pair of biotin and dinitrophenol 5'-labeled primers, the reaction mixture was applied to a microtiter well precoated with streptavidin. Thereafter, bound PCR products were detected colorimetrically with alkaline phosphatase-conjugated anti-dinitrophenol antibody. The extraction of DNA from staphylococcal cells for PCR was simplified so that it could be performed within one tube. The total assay, including PCR, took less than 3 h. The sensitivity of mecA gene detection ranged from greater than 5 x 10(2) CFU per tube for Staphylococcus aureus to greater than 5 x 10(3) CFU per tube for Staphylococcus epidermidis. Genotyping results obtained by ED-PCR of 161 tested strains from the colonies (97 strains of S. aureus and 64 strains of coagulase-negative staphylococci) were compared with the phenotypic susceptibilities of the strains to oxacillin. The results of ED-PCR showed excellent agreement with the MICs of oxacillin with very few exceptions; only one strain of S. aureus and two strains of coagulase-negative staphylococci were found to possess the mecA gene, which was discrepant with their phenotypes. Fifty-five blood culture samples were also tested by ED-PCR. For staphylococcal isolates in 33 of the cultures, oxacillin MICs were >4 microgram/ml; 31 of the 33 staphylococcal isolates were determined by ED-PCR to be mecA gene positive. These results suggest that ED-PCR can be used with reasonable confidence in the clinical microbiological laboratory.